Epigenetic inhibition of adaptive bypass responses to lapatinib by targeting BET Bromodomains. (2nd January 2016) - Stuhlmiller, Timothy J.; Miller, Samantha M.; Johnson, Gary L.
ABSTRACT: The characterization of kinases as oncogenic drivers has led to more than 30 FDA-approved targeted kinase inhibitors for cancer treatment. Unfortunately, these therapeutics fail to have clinical durability because of adaptive responses from the kinome and transcriptome that bypass inhibition of the targeted pathway. In our recent work, we describe a method to prevent these adaptive responses at an epigenetic level, generating a durable response to kinase inhibition.